Imagery and verbal thought during rumination and distraction: Does imagery amplify affective response?. Issue 5 (4th July 2019) - Lawrence, Hannah R.; Schwartz-Mette, Rebecca A.
ABSTRACT: Rumination has long been considered a verbal thought process, though emerging evidence suggests that some individuals dwell on maladaptive imagery. This series of studies evaluated imagery and verbal thought during experimentally induced rumination and distraction. In Study 1, imagery and verbal thought during rumination resulted in similar increases in negative affect. Greater imagery during distraction, on the other hand, was associated with greater decreases in negative affect while verbal thought was not related to affect change. Given that greater verbal thought was reported in the rumination condition and greater imagery was reported in the distraction condition, Study 2 evaluated whether the rumination/distraction induction was confounded by concurrent induction of imagery or verbal thought. The rumination prompts induced both rumination and verbal thought and the distraction prompts induced both distraction and imagery. Using a revised induction, Study 3 tested whether imagery and verbal thought during rumination and distraction impacted affective response. Rumination maintained negative affect and distraction relieved negative affect, regardless of the degree to which imagery or verbal thought was experienced. This paper provides evidence that imagery-based rumination is just as impairing as verbally-based rumination and highlights imagery-based distraction as a potentially effective alternative to rumination.